Analisis Koordinasi Pelaksanaan Rencana Tata Ruang Wilayah Kabupaten Pati - Hapsari, Katrin Winarsih; Djumiarti, Titik; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2014)
Issues such as the absence of rules governing the coordination of local government implementation of the Pati RTRW implementation only as coordination meeting (coordination meeting of BKPRD), and the level of attendance of participants minimal rakor, as well as the presence of the participants in the replacement which does not have capacity rakor and capabilities into the background of this research. This research aims to analyze the implementation coordination RTRW Pati and do know the factors that hinder coordination. This research uses qualitative research methods are purely descriptive. The subjects in this study consists of 6 (six) main informant. Unfortunately, the use of additional resources have not been used in the coordination of the implementation of RTRW.